Industrial and energy solid waste-based pavement base disease rapid repair material and preparation method thereof
Patent Information
- Application Number
- CN202512052247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-30
AI Technical Summary
不仅占用大量土地,还易引发土壤、水体、大气污染等环境问题,亟须拓展消纳路径
[0024](1)本发明以硫铝酸盐水泥体系为主,复配经煅烧激活的铝尾矿、麦饭石和赤泥等富硅铝材料,同时采用电石渣、锂矿渣、废旧锂离子电池正极材料等固废及磷酸铁锂进行化学激发,构建水硬性胶凝材料体系,该体系具有良好的水硬性,可形成具有一定力学强度的固结体,在一定程度上减少了硫铝酸盐水泥的用量。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a rapid repair material for road base layer defects based on industrial and energy solid waste and its preparation method. Background Technology
[0002] Semi-rigid base courses are characterized by low engineering costs, convenient construction, and superior material performance. In my country's high-grade highway construction, cement-stabilized crushed stone and other semi-rigid materials are often used as the base structure for asphalt pavements. However, under traffic loads and adverse weather conditions, semi-rigid base courses are prone to various defects, such as fractures, breakage, cracks, and water damage, leading to a decline in pavement traffic function and affecting passage. When the subgrade has weak soil or insufficient compaction, resulting in insufficient bearing capacity, uneven settlement occurs under repeated heavy vehicle traffic. This can easily cause the semi-rigid base course to fracture or even pulverize, further affecting pavement quality.
[0003] Subgrade defects are structural damage to roads. Their appearance indicates that the road's structural load-bearing capacity no longer meets usage requirements, necessitating treatment by road maintenance units. Subgrade defects can also reflect onto the road surface, causing surface cracking and affecting pedestrian and vehicle comfort. The formation of reflective defects also signifies broken concrete slabs or fractures in the asphalt surface layer. Rainwater can seep into the subgrade through these cracks, and under the dynamic load of traffic, erode the subgrade mixture, causing aggregate spalling and loosening, thus exacerbating subgrade damage.
[0004] The treatment of road base layer defects has always been a key focus in the road maintenance field both domestically and internationally. Traditional methods involve a "groping" approach, requiring the complete milling of the base layer and above before laying a new base layer and surface. Common materials for this new base layer are ordinary cement concrete or cement-stabilized crushed stone. This method has significant drawbacks: firstly, it involves a massive amount of work and a long construction period (the curing period alone requires more than 7 days); secondly, it requires complete road closures, severely impacting traffic flow on highways and first-class roads with high traffic volumes, making it extremely unsuitable. Grouting and injection techniques for rapid, trenchless road repair and reinforcement are currently an effective method. By injecting grouting material into cracks or pores in the subgrade and base layer, reinforcement is achieved, improving the load-bearing capacity of the base layer. Commonly used grouting materials are cement-based, but these materials suffer from poor stability, poor fluidity, low early strength, and long setting time. Furthermore, cement production causes environmental pollution. Therefore, there is an urgent need to provide a new type of repair material that has good fluidity, can quickly form load-bearing strength, has early strength and fast hardening, and has excellent early and late mechanical properties.
[0005] Meanwhile, with the rapid development of industries such as chemicals, steel, coal power, and non-ferrous metals in recent years, the output of industrial solid waste has continued to climb, with an annual production of nearly 4 billion tons and a cumulative stockpile exceeding 60 billion tons. This not only occupies a large amount of land but also easily causes environmental problems such as soil, water, and air pollution, necessitating the expansion of disposal pathways.
[0006] This invention addresses the bottleneck problem of material performance in existing road structural defects by rationally selecting materials and combining them with specific processes to prepare a green and environmentally friendly rapid repair material for road pavement base structural defects. It has advantages such as reducing production costs, saving energy and reducing emissions, disposing of solid waste, and quickly opening to traffic. Summary of the Invention
[0007] To address the shortcomings of the existing technologies, one of the objectives of this invention is to provide a rapid repair material for road base layer defects based on industrial and energy solid waste. This invention, through reasonable material selection and specific processes, prepares a rapid repair material for road base layer defects based on solid waste. This repair material has good fluidity and can quickly form load-bearing strength within 4 hours. It has characteristics such as early strength and rapid hardening, and excellent early and late mechanical properties. At the same time, it can absorb a large amount of industrial and energy solid waste.
[0008] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0009] A rapid repair material for road base layer defects based on industrial and energy solid waste comprises the following components in parts by weight: 20-30 parts sulfoaluminate cement, 3-5 parts sintered red mud, 3-5 parts maifanite, 5-8 parts aluminum tailings powder, 2-4 parts lithium slag, 3-4 parts calcium carbide slag, 20-25 parts calcined bauxite, 5-10 parts aluminum tailings, 10-15 parts aluminum sludge ceramsite, 0.5-1 part borax, 0.5-1 part tartaric acid, 3-6 parts waste lithium-ion battery cathode material, 0.3-0.5 parts lithium iron phosphate, 4-6 parts titanium gypsum, and 2-3 parts polycarboxylate superplasticizer.
[0010] This invention primarily utilizes a sulfoaluminate cement system, compounded with silicon-aluminate-rich materials such as calcined and activated aluminum tailings, maifanite, and red mud. Simultaneously, it employs solid wastes such as carbide slag, lithium ore slag, and spent lithium-ion battery cathode materials, along with lithium iron phosphate, for chemical activation to construct a hydraulic cementitious material system. This system exhibits excellent hydraulic properties, forming a solidified body with a certain mechanical strength, effectively reducing the amount of sulfoaluminate cement required. Furthermore, this invention selects silicon-aluminate-rich materials such as calcined bauxite, aluminum tailings, and aluminum sludge ceramsite as composite aggregates. These aggregates, under the synergistic activation effect of spent lithium-ion battery cathode materials and carbide slag, can replace natural aggregates. Moreover, compared to traditional natural aggregates such as limestone and basalt, this activated composite aggregate significantly enhances the interfacial bonding performance with cementitious materials, thereby improving the overall mechanical stability, volume stability, and durability of the material. Furthermore, the combination of strength, shape, and particle size of calcined bauxite, aluminum tailings, and aluminum sludge ceramsite gives the material excellent flow properties and mechanical properties.
[0011] Preferably, the specific surface area of the sintered red mud, maifanite, aluminum tailings powder, lithium slag, and carbide slag is ≥300m². 2 / kg.
[0012] Preferably, the calcined bauxite has a particle size of 3–10 mm and a density ≥ 2.9 g / cm³. 3 Elastic modulus ≥200GPa, Los Angeles abrasion loss ≤22%, crushing value ≤18%.
[0013] Preferably, the aluminum tailings have a particle size of 3-10 mm, a Los Angeles abrasion loss of ≤35%, and a crushing value of ≤30%.
[0014] Preferably, the technical specifications of the aluminum sludge ceramsite meet the requirements of T / CIPR 0014-2023 "Aluminum Sludge Ceramsite", with a density grade of 800, spherical shape, and particle size of 3-10 mm.
[0015] Preferably, the Li content in the waste lithium-ion battery cathode material is ≥4.0%.
[0016] Preferably, the waste lithium-ion batteries include at least one of lithium iron phosphate batteries, lithium nickel cobalt manganese oxide batteries, lithium cobalt oxide batteries, lithium nickel oxide batteries, and lithium manganese oxide batteries.
[0017] Preferably, the polycarboxylate superplasticizer is a powdered polycarboxylate superplasticizer with a water reduction rate of ≥25%.
[0018] Another object of the present invention is to provide a method for preparing the aforementioned rapid repair material for road base layer defects, comprising the following steps:
[0019] S1. Weigh each component according to the specified weight proportions, mix the sintered red mud, maifanite, aluminum tailings powder, and lithium slag, and then grind them to a specific surface area ≥ 300 m². 2 / kg, then calcined at 700~900℃ for 1~3h; then ground with tartaric acid, borax, lithium iron phosphate and calcium carbide slag until the specific surface area is ≥400m². 2 / kg, yielding component A;
[0020] S2. Grind sulfoaluminate cement, titanium gypsum, and polycarboxylate superplasticizer to a specific surface area ≥ 350 m². 2 / kg, yielding component B;
[0021] S3. Mix calcined bauxite, aluminum tailings, aluminum sludge ceramsite, waste lithium-ion battery cathode material and calcium carbide slag evenly to obtain component C;
[0022] S4. Mix components A, B, and C evenly to obtain the rapid repair material for road base layer defects.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] (1) This invention is based on a sulfoaluminate cement system, compounded with silicon-rich aluminum materials such as calcined and activated aluminum tailings, maifanite and red mud, and chemically activated solid waste such as carbide slag, lithium slag, waste lithium-ion battery cathode materials and lithium iron phosphate to construct a hydraulic cementitious material system. This system has good hydraulic properties and can form a solid body with certain mechanical strength, which reduces the amount of sulfoaluminate cement used to a certain extent.
[0025] (2) This invention selects silicon-aluminum-rich materials such as calcined bauxite, aluminum tailings, and aluminum sludge ceramsite as composite aggregates. These aggregates can replace natural aggregates under the synergistic activation effect of waste lithium-ion battery cathode materials and carbide slag. Moreover, compared with traditional natural aggregates such as limestone and basalt, this activated composite aggregate can significantly enhance the interfacial bonding performance with cementitious materials, thereby improving the overall mechanical stability, volume stability, and durability of the material.
[0026] (3) The present invention enables the material to have excellent flow properties and mechanical properties simultaneously by combining the strength, shape and particle size of calcined bauxite, aluminum tailings and aluminum sludge ceramsite.
[0027] (4) This invention uses sulfoaluminate cement as a base, combined with calcined and chemically activated aluminum tailings, maifanite, and red mud as a cementing system, and calcined bauxite, aluminum tailings, and aluminum sludge ceramsite synergistically activated by waste lithium-ion battery cathode materials and carbide slag as composite aggregates, to successfully prepare a rapid repair material for solid waste-based road base layer defects. This repair material has good fluidity and can quickly form load-bearing strength within 4 hours. It has the characteristics of early strength and rapid hardening, and excellent early and late mechanical properties. At the same time, it can absorb a large amount of industrial and energy solid waste. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] The present invention relates to a rapid repair material for road base layer defects based on industrial and energy solid waste, comprising the following components in parts by weight: 20-30 parts of sulfoaluminate cement, 3-5 parts of sintered red mud, 3-5 parts of maifanite, 5-8 parts of aluminum tailings powder, 2-4 parts of lithium slag, 3-4 parts of carbide slag, 20-25 parts of calcined bauxite, 5-10 parts of aluminum tailings, 10-15 parts of aluminum sludge ceramsite, 0.5-1 part of borax, 0.5-1 part of tartaric acid, 3-6 parts of waste lithium-ion battery cathode material, 0.3-0.5 parts of lithium iron phosphate, 4-6 parts of titanium gypsum, and 2-3 parts of polycarboxylate superplasticizer.
[0030] In some embodiments, the specific surface area of the sintered red mud, maifanite, aluminum tailings powder, lithium slag, and carbide slag is ≥300 m². 2 / kg;
[0031] In some embodiments, the calcined bauxite has a particle size of 3–10 mm and a density ≥2.9 g / cm³. 3 Elastic modulus ≥200GPa, Los Angeles abrasion loss ≤22%, crushing value ≤18%;
[0032] In some embodiments, the aluminum tailings have a particle size of 3–10 mm, a Los Angeles abrasion loss of ≤35%, and a crushing value of ≤30%.
[0033] In some embodiments, the technical specifications of the aluminum sludge ceramsite meet the requirements of T / CIPR 0014-2023 "Aluminum Sludge Ceramsite", which specifies a density grade of 800, spherical shape, and particle size of 3-10 mm.
[0034] In some embodiments, the Li content in the cathode material of the waste lithium-ion battery is ≥4.0%; the waste lithium-ion battery can be selected from any one or more of lithium iron phosphate batteries, lithium nickel cobalt manganese oxide batteries, lithium cobalt oxide batteries, lithium nickel oxide batteries, and lithium manganese oxide batteries, as long as the Li content in the cathode material of the waste lithium-ion battery is ≥4.0%.
[0035] In some embodiments, the polycarboxylate superplasticizer is a powdered polycarboxylate superplasticizer with a water reduction rate ≥25%;
[0036] In some embodiments, the preparation method of the rapid repair material for road base layer defects includes the following steps:
[0037] S1. Weigh each component according to the specified weight proportions, mix the sintered red mud, maifanite, aluminum tailings powder, and lithium slag, and then grind them to a specific surface area ≥ 300 m². 2 / kg, then calcined at 700~900℃ for 1~3h; then ground with tartaric acid, borax, lithium iron phosphate and calcium carbide slag until the specific surface area is ≥400m². 2 / kg, yielding component A;
[0038] S2. Grind sulfoaluminate cement, titanium gypsum, and polycarboxylate superplasticizer to a specific surface area ≥ 350 m². 2 / kg, yielding component B;
[0039] S3. Mix calcined bauxite, aluminum tailings, aluminum sludge ceramsite, waste lithium-ion battery cathode material and calcium carbide slag evenly to obtain component C;
[0040] S4. Mix components A, B, and C evenly to obtain the rapid repair material for road base layer defects.
[0041] The physicochemical data of the industrial solid waste raw materials used in the embodiments of the present invention are shown in Table 1 below.
[0042] Table 1. Main chemical composition (wt%) of raw materials used in the embodiments of the present invention
[0043]
[0044] Example 1
[0045] This embodiment provides a method for preparing a rapid repair material for road base layer defects based on industrial and energy solid waste, including the following steps:
[0046] S1. Mix 5 parts maifanite, 5 parts aluminum tailings powder, 3 parts sintered red mud, and 2 parts lithium slag using a ball mill until the specific surface area meets the requirement of 350 m². 2 / kg, then calcined at 800℃ for 2 hours, and then ground in a ball mill with 0.5 parts tartaric acid, 0.6 parts borax, 0.3 parts lithium iron phosphate, and 2 parts calcium carbide slag until the specific surface area is not less than 400m². 2 / kg, reserved as component A;
[0047] S2. 28 parts of sulfoaluminate cement, 4 parts of titanium gypsum, and 3 parts of polycarboxylate superplasticizer are premixed and ball-milled until a specific surface area of 350 m² is achieved. 2 / kg, reserved as component B;
[0048] S3. Mix 20 parts of calcined bauxite, 6 parts of aluminum tailings, 15 parts of aluminum sludge ceramsite, 3 parts of recycled waste lithium-ion battery cathode material, and 2 parts of calcium carbide slag evenly using a forced mixer, and set aside as component C.
[0049] S4. Using a forced mixer, add component C, component B, and component A in sequence, and mix for 5 minutes to obtain a rapid repair material for road base layer defects.
[0050] Example 2
[0051] This embodiment provides a method for preparing a rapid repair material for road base layer defects based on industrial and energy solid waste, including the following steps:
[0052] S1. Mix 3 parts maifanite, 8 parts aluminum tailings powder, 5 parts sintered red mud, and 4 parts lithium slag using a ball mill until the specific surface area meets the requirement of 300 m². 2 / kg, then calcined at 800℃ for 2 hours, and then ground with 1.0 part tartaric acid, 1.0 part borax, 0.5 part lithium iron phosphate, and 2 parts calcium carbide slag in a ball mill until the specific surface area is not less than 400m². 2 / kg, reserved as component A;
[0053] S2. 25 parts of sulfoaluminate cement, 6 parts of titanium gypsum, and 2 parts of polycarboxylate superplasticizer are premixed and ball-milled until a specific surface area of 350 m² is achieved. 2 / kg, reserved as component B;
[0054] S3. Mix 25 parts of calcined bauxite, 10 parts of aluminum tailings, 10 parts of aluminum sludge ceramsite, 5 parts of recycled waste lithium-ion battery cathode material, and 2 parts of calcium carbide slag evenly using a forced mixer, and set aside as component C.
[0055] S4. Using a forced mixer, add component C, component B, and component A in sequence, and mix for 5 minutes to obtain a rapid repair material for road base layer defects.
[0056] Comparative Example 1
[0057] The preparation method of the rapid repair material for road base layer diseases in this comparative example is basically the same as that in Example 1, except that the maifanite is omitted in step S1 and the weight of aluminum tailings powder is adjusted to 10 parts.
[0058] Comparative Example 2
[0059] The preparation method of the rapid repair material for road base layer defects in this comparative example is basically the same as that in Example 1, except that lithium iron phosphate is omitted in step S1 and the weight of lithium slag is adjusted to 2.3 parts.
[0060] Comparative Example 3
[0061] The preparation method of the rapid repair material for road base layer defects in this comparative example is basically the same as that in Example 1, except that the titanium gypsum in step S2 is replaced with an equal amount of phosphogypsum.
[0062] Comparative Example 4
[0063] The preparation method of the rapid repair material for road base layer defects in this comparative example is basically the same as that in Example 1, except that step S3 is omitted, and component C is replaced with an equal amount of limestone with a particle size of 3-10 mm.
[0064] Comparative Example 5
[0065] The preparation method of the rapid repair material for road base layer diseases in this comparative example is basically the same as that in Example 1, except that the recycling of waste lithium-ion battery cathode material is omitted in step S3, and the weight of carbide slag is adjusted to 5 parts accordingly.
[0066] Comparative Example 6
[0067] The preparation method of the rapid repair material for road base layer diseases in this comparative example is basically the same as that in Example 1, except that aluminum sludge ceramsite is omitted in step S3, and the weight of aluminum tailings is adjusted to 21 parts accordingly.
[0068] Comparative Example 7
[0069] The preparation method of the rapid repair material for road base layer diseases in this comparative example is basically the same as that in Example 1, except that the calcination of bauxite is omitted in step S3, and the weight of aluminum tailings is adjusted to 26 parts accordingly.
[0070] Test case
[0071] The repair materials obtained in the examples and comparative examples were mixed with water at a ratio of 1:0.2, and their relevant properties were tested according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" and GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". The performance test results are shown in Table 2.
[0072] Table 2 Performance test results of repair materials
[0073]
[0074] As shown in Table 2, the repair material of the present invention has good fluidity and workability, and can quickly form load-bearing strength within 4 hours, while also having high strength in the later stage.
[0075] Comparing Example 1 and Comparative Example 1 reveals that using maifanite, aluminum tailings, and red mud to construct a hydraulic cementitious material system can improve the flexural and compressive strength of the material at different ages. Maifanite provides silicate components to the cementitious components, affecting the cementitious ability of the hydration products and thus impacting the mechanical load-bearing capacity. Comparing Example 1 and Comparative Example 2 shows that compared to using lithium slag alone for activation, synergistic activation with lithium iron phosphate and lithium slag can improve the early strength of the material, especially the compressive and flexural strength at 4 hours. Comparing Example 1 and Comparative Example 3 reveals that replacing titanium gypsum with phosphogypsum, which is a byproduct of wet phosphoric acid production and contains residual phosphoric acid, interferes with the hydration reaction of aluminate minerals and slows down the reaction process, is detrimental. Titanium gypsum, on the other hand, is a byproduct of titanium dioxide production via the sulfuric acid process and contains sulfates and other substances, which promote the hydration reaction of aluminate and silicate minerals. Therefore, replacing titanium gypsum with phosphogypsum affects the early strength of concrete and reduces its initial mechanical properties. Comparing Example 1 and Comparative Example 4 shows that, compared to traditional natural aggregate limestone, the activated composite aggregate used in this invention significantly enhances the interfacial bonding performance with cementitious materials, promotes the adhesion of cementitious products and the aggregate framework into a unified whole, collaboratively bearing external loads and resisting destructive stress, thereby improving the overall mechanical properties of the material. Comparing Example 1 and Comparative Example 5 reveals that, compared to using calcium carbide slag alone for activation, the synergistic activation of calcined bauxite, aluminum tailings, and aluminum sludge ceramsite using recycled waste lithium-ion battery cathode material and calcium carbide slag improves the 4-hour compressive and flexural strength of the material, significantly promoting early-age mechanical properties without degradation over long-term use. Comparing Example 1 and Comparative Examples 6-7 shows that omitting aluminum sludge ceramsite reduces the material's flow properties, while omitting calcined bauxite reduces its mechanical properties. This invention, through the synergistic combination of the strength, shape, and particle size of calcined bauxite, aluminum tailings, and aluminum sludge ceramsite, enables the material to possess both excellent flow properties and mechanical properties, while also improving the utilization rate of solid waste.
[0076] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A rapid repair material for road base layer defects based on industrial and energy solid waste, characterized in that, The composition comprises the following components in parts by weight: 20-30 parts sulfoaluminate cement, 3-5 parts sintered red mud, 3-5 parts maifanite, 5-8 parts aluminum tailings powder, 2-4 parts lithium slag, 3-4 parts calcium carbide slag, 20-25 parts calcined bauxite, 5-10 parts aluminum tailings, 10-15 parts aluminum sludge ceramsite, 0.5-1 part borax, 0.5-1 part tartaric acid, 3-6 parts waste lithium-ion battery cathode material, 0.3-0.5 parts lithium iron phosphate, 4-6 parts titanium gypsum, and 2-3 parts polycarboxylate superplasticizer.
2. The rapid repair material for road base layer defects according to claim 1, characterized in that, The specific surface area of the sintered red mud, maifanite, aluminum tailings powder, lithium slag, and carbide slag is ≥300 m². 2 / kg.
3. The rapid repair material for road base layer defects according to claim 1, characterized in that, The calcined bauxite has a particle size of 3–10 mm and a density ≥2.9 g / cm³. 3 Elastic modulus ≥200GPa, Los Angeles abrasion loss ≤22%, crushing value ≤18%.
4. The rapid repair material for road base layer defects according to claim 1, characterized in that, The aluminum tailings have a particle size of 3-10 mm, a Los Angeles abrasion loss of ≤35%, and a crushing value of ≤30%.
5. The rapid repair material for road base layer defects according to claim 1, characterized in that, The technical specifications of the aluminum sludge ceramsite meet the requirements of T / CIPR 0014-2023 "Aluminum Sludge Ceramsite".
6. The rapid repair material for road base layer defects according to claim 1, characterized in that, The Li content in the cathode material of the waste lithium-ion battery is ≥4.0%.
7. The rapid repair material for road base layer defects according to claim 1, characterized in that, The polycarboxylate superplasticizer is a powdered polycarboxylate superplasticizer with a water reduction rate of ≥25%.
8. The method for preparing the rapid repair material for road base layer defects according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Weigh each component according to the specified weight proportions, mix the sintered red mud, maifanite, aluminum tailings powder, and lithium slag, and then grind them to a specific surface area ≥ 300 m². 2 / kg, then calcined at 700~900℃ for 1~3h; then ground with tartaric acid, borax, lithium iron phosphate and calcium carbide slag until the specific surface area is ≥400m². 2 / kg, yielding component A; S2. Grind sulfoaluminate cement, titanium gypsum, and polycarboxylate superplasticizer to a specific surface area ≥ 350 m². 2 / kg, yielding component B; S3. Mix calcined bauxite, aluminum tailings, aluminum sludge ceramsite, waste lithium-ion battery cathode material and calcium carbide slag evenly to obtain component C; S4. Mix components A, B, and C evenly to obtain the rapid repair material for road base layer defects.